2020
DOI: 10.1016/j.chembiol.2020.01.010
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR-Mediated Protein Tagging with Nanoluciferase to Investigate Native Chemokine Receptor Function and Conformational Changes

Abstract: Highlights d Utilizing CRISPR/Cas9-mediated knockin to investigate GPCR function d NanoBRET ligand binding at CRISPR/Cas9 genome-edited chemokine receptors d Real time monitoring of live cell interactions between native CXCR4 and b-arrestin2 d Development of an approach to examine extracellular CXCR4 conformational changes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
74
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 54 publications
(86 citation statements)
references
References 52 publications
(74 reference statements)
12
74
0
Order By: Relevance
“…NanoBRET ligand binding also confirmed that the receptor could tolerate the addition LgBiT via N-terminal fusion without the loss of binding affinity of the fluorescent ligand CXCL12-AF647. This tolerance is in agreement with previous studies on NanoBRET-based ligand binding with CXCR4 receptor tagged on the N-terminus with full-length NanoLuc (White et al, 2020). Therefore, even though the N-terminus of CXCR4 is involved in the binding of CXCL12 (Crump et al, 2018;Gupta et al, 2001), our NanoBRET binding data showed that N-terminally fused LgBiT did not interfere with ligand binding.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…NanoBRET ligand binding also confirmed that the receptor could tolerate the addition LgBiT via N-terminal fusion without the loss of binding affinity of the fluorescent ligand CXCL12-AF647. This tolerance is in agreement with previous studies on NanoBRET-based ligand binding with CXCR4 receptor tagged on the N-terminus with full-length NanoLuc (White et al, 2020). Therefore, even though the N-terminus of CXCR4 is involved in the binding of CXCL12 (Crump et al, 2018;Gupta et al, 2001), our NanoBRET binding data showed that N-terminally fused LgBiT did not interfere with ligand binding.…”
Section: Discussionsupporting
confidence: 93%
“…Taken together, these data show that the binding of AMD3100 and IT1t to N-terminally tagged CXCR4 receptors can inhibit VUN400-HiBiT binding to ECL2 of the receptor, probably as a result of a conformational change. This is consistent with a reciprocal negative allosteric interaction between the binding sites for AMD3100 and VUN400-HiBiT, and the known ability of small molecule inhibitors such as AMD3100 to induce conformational rearrangement of the extracellular domains of CXCR4 (White et al, 2020) and modulate monoclonal antibody binding (Carnec et al, 2005;Rosenkilde et al, 2004). The conformational changes involving ECL2 induced by both CXCL12 and AMD3100 in LgBiT-CXCR4 could be followed in real-time in living cells following pre-equilibration with VUN400-HiBiT bound ( Figure 6) and these changes were much slower than the ability of both ligands to induce dissociation of a fluorescent analogue of CXCL12 from the receptor.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…However, these studies used either purified luciferase-tagged CXCL12 or cells secreting exogenous luciferase-tagged CXCL12 to monitor binding by luciferase complementation or changes in luminescence, rather than endogenously expressed CXCL12. More recently, we have demonstrated that ligand binding to CXCR4 and ACKR3 tagged with the Nanoluciferase (NLuc) can be monitored in live cells using CXCL12 labelled with AF647 and NanoBRET 15 . It has been shown that a split-version of NLuc can be used to investigate peptide ligand binding to relaxin peptide family receptor 3 and 4 by NLuc complementation 16 .…”
Section: Introductionmentioning
confidence: 99%